Setting up a clinical skills learning facility. - Bradley P; Postlethwaite K (Medical Education)
This paper outlines the considerations to be made when establishing a clinical skills learning facility. Establishing a clinical skills learning facility is a complex project with many possible options to be considered. A number of professional groups, undergraduate or postgraduate, may be users. Their collaboration can have benefits for funding, uses and promotion of interprofessional education. Best evidence and educational theory should underpin teaching and learning. The physical environment should be flexible to allow a range of clinical settings to be simulated and to facilitate a range of teaching and learning methods, supported by computing and audio-visual resources. Facilities should be available to encourage self-directed learning. The skills programme should be designed to support the intended learning outcomes and be integrated within the overall curriculum, including within the assessment strategy. Teaching staff may be configured in a number of ways and may be drawn from a variety of backgrounds. Appropriate staff development will be required to ensure consistency and quality of teaching with monitoring and evaluation to assure appropriate standards. Patients can also play a role, not only as passive teaching material, but also as teachers and assessors. Clinical, diagnostic and therapeutic equipment will be required, as will models and manikins. The latter will vary from simple part task trainers to highly sophisticated human patient simulators. Care must be taken when choosing equipment to ensure it matches specified requirements for teaching and learning. Detailed planning is required across a number of domains when setting up a clinical skills learning facility.